2018
DOI: 10.1002/chem.201801578
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Probes for Imaging Fibrosis and Fibrogenesis

Abstract: Fibrosis, or the accumulation of extracellular matrix molecules that make up scar tissue, is a common result of chronic tissue injury. Advances in the clinical management of fibrotic diseases have been hampered by the low sensitivity and specificity of noninvasive early diagnostic options, lack of surrogate end points for use in clinical trials, and a paucity of noninvasive tools to assess fibrotic disease activity longitudinally. Hence, the development of new methods to image fibrosis and fibrogenesis is a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 111 publications
(188 reference statements)
1
44
0
1
Order By: Relevance
“…Additional profibrotic molecules which could be of interest for targeted nuclear imaging include extracellular matrix proteins, for example, collagens, fibronectin or fibroblast activation protein 3 52. However, in contrast to our selected imaging targets, radiotracers for these molecules have so far only been validated in animal models53 54 or in human non-ILD conditions 55–57.…”
Section: Discussionmentioning
confidence: 99%
“…Additional profibrotic molecules which could be of interest for targeted nuclear imaging include extracellular matrix proteins, for example, collagens, fibronectin or fibroblast activation protein 3 52. However, in contrast to our selected imaging targets, radiotracers for these molecules have so far only been validated in animal models53 54 or in human non-ILD conditions 55–57.…”
Section: Discussionmentioning
confidence: 99%
“…(a) Chemical structures of developed collagen‐targeted probes EP‐3533 and CM‐101 for molecular MR imaging of fibrosis. (b) MR images of a control and fibrotic mouse and its correlation with histological characterization (collagen content), post injection of EP‐3533 in CCl 4 ‐induced liver fibrosis mouse model (Desogere, Montesi, & Caravan, )…”
Section: Ecm Targeted Contrast Agents Based On Conjugationmentioning
confidence: 99%
“…A noninvasive method to identify patients with disease, to identify regions of active disease activity, and/or to identify patients likely to progress rapidly would also have benet in developing new therapeutics for IPF because patients could be better stratied for trial enrolment, and early measures of treatment response may be observed. [10][11][12][13] We are interested in developing molecular magnetic resonance (MR) probes to asses IPF disease activity by targeting biochemical features of active brosis (i.e. brogenesis).…”
Section: Introductionmentioning
confidence: 99%
“…A noninvasive method to identify patients with disease, to identify regions of active disease activity, and/or to identify patients likely to progress rapidly would also have benefit in developing new therapeutics for IPF because patients could be better stratified for trial enrolment, and early measures of treatment response may be observed. 10 13 …”
Section: Introductionmentioning
confidence: 99%